Indicators on Terrestrial and Marine Protected Areas Methodology and Results for OECD and G20 countries - Mackie, Alexander (OECD Environment Working Papers, 2017)
This paper details a methodology for calculating the extent of terrestrial and marine protected areas recorded in the World Database on Protected Areas by country, type and IUCN management categories. The method allows the data on protected areas to be summarised in a harmonised and more detailed way than is currently available, without requiring any additional reporting by countries. When used in combination with other information about protected areas, this new indicator can help better understand the extent and focus of countries' conservation efforts